A STUDY ON THE ABILITY OF THE ENGLISH DEPARTMENT STUDENTS OF FKIP UNIVERSITAS RIAU IN WRITING AN E-MAIL - Khairani Anisa; Erni Erni; Dahnilsyah Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Nowadays, e-mail is one of general ways to communicate or to send messages between students and lecturer in academic purposes. This study aims to find out the ability of the English Department students of FKIP Universitas Riau in writing an e-mail to the lecturer. This study used the second semester students in academic year 2018/2019 as the population. Simple random sampling used to take the sample. The sample of this study was 37 students. Writing test used for the instrument. Data collected by received 37 e-mails written by the students. The data included descriptive quantitative method. From the data analysis, it was found that the ability of second semester students of the English Department FKIP Universitas Riau was in good level. The score of each aspects of e-mail writing was be analyzed of this study. The high score are content/idea and vocabulary. The low score are subject line, mechanics and grammar. Therefore, the students are expected to study and practice more how to write an e-mail to the lecturer with concerning some e-mail format, subject line, format and structure, mechanics, content/idea, grammar and vocabulary.Key Words: Ability, Writing, E-Mail.